2014
DOI: 10.1103/physrevb.89.060401
|View full text |Cite
|
Sign up to set email alerts
|

Critical scaling in the cubic helimagnetCu2OSeO3

Abstract: We present a detailed ac susceptibility investigation of the fluctuation regime in the insulating cubic helimagnet Cu 2 OSeO 3 . For magnetic fields μ 0 H 200 mT, and over a wide temperature (T ) range, the system behaves according to the scaling relations characteristic of the classical three-dimensional Heisenberg model. For lower magnetic fields, the scaling is preserved only at higher T and becomes renormalized in a narrow-T range above the transition temperature. Contrary to the well-studied case of MnSi,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
41
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 16 publications
7
41
0
1
Order By: Relevance
“…Such a change in curvature was experimentally found in MnSi [11] in addition to the latent heat associated with the weak first-order transition [12,13]. Subsequently, it was demonstrated that other cubic helimagnets with the same space group like Cu 2 OSeO 3 [14] and FeCo 1−x Si x [15] show similar behavior.…”
Section: Introductionmentioning
confidence: 61%
“…Such a change in curvature was experimentally found in MnSi [11] in addition to the latent heat associated with the weak first-order transition [12,13]. Subsequently, it was demonstrated that other cubic helimagnets with the same space group like Cu 2 OSeO 3 [14] and FeCo 1−x Si x [15] show similar behavior.…”
Section: Introductionmentioning
confidence: 61%
“…This peculiar scattering occurs in a region dominated by precursor phenomena that have been probed with a wide range of experimental techniques [9][10][11][14][15][16]. Similar precursor phenomena have also been found in FeGe [17,18] and the multiferroic Cu 2 OSeO 3 [19][20][21] and are thus of general relevance to chiral magnetism.…”
mentioning
confidence: 67%
“…At still larger fields the moments become disordered but fieldpolarized. The dashed line extending diagonally into the paramagnetic regime represents a cross-over from such a field-polarized region and a fully disordered paramagnetic state at high temperatures which has been recently shown to follow a classical 3D Heisenberg scaling 14 . The SkL pocket is located within the conical phase, spanning 2 − 3 K just below the order-disorder line between points P 2 and P 3 .…”
Section: Resultsmentioning
confidence: 99%